Developing an advanced understanding of Au-U-C associations in the Witwatersrand Basin : using traditional and experimental techniques - Woods, Tremain (My University, 2017)
The Witwatersrand Basin is the single largest gold source ever found. Gold exhibits a strong association with carbon and as much as 40% of the gold mined from the metasedimentary basin is found in carbon-bearing reefs. Carbon also contains high concentrations of uranium minerals. Although the carbon, gold and uranium association is well-documented, there is little consensus about the formation of these associations. Thus, a detailed geological investigation was undertaken on material from 12 carbon-bearing reefs throughout the Central Rand Group from across the Witwatersrand Basin. Concurrently a novel experimental component of the investigation was conducted in an attempt to simulate, for the first time ever, the Au-U-C associations in the Witwatersrand Basin. Petrography revealed that in more than 60 samples from carbon-bearing Witwatersrand Reefs, gold most often occurred between carbon spindles, as minor inclusions within carbon spindles and as coatings to the carbon forms. Furthermore, gold within the conglomerates occurred as veinlets, rims on oxide grains, as micro-particles in phyllosilicates and secondary quartz and as inclusions in secondary pyrite grains. These textures were interpreted as secondary features formed during metamorphism and alteration of the Basin. Hydrocarbons displayed textures that were also interpreted as being secondary; these included nodules that infilled interstices within the reef matrix and multiple phases of hydrocarbon enclosed within spindles comprising carbon seams. Electron microscope images were taken of a hydrothermal carbon nodule enclosed in cubic pyrite. The images revealed sheet-like hydrocarbons and fibrous/tube-like forms. Critically, the hydrothermal carbon nodule also contained micro-particulate crystalline gold and pyrite within vesicles or gas bubbles within in the nodule. In the carbon seams, uraninite occurred within the spindles. The uraninite appeared fragmented and displaced by hydrocarbon growth structures. Therefore, it was suggested that uraninite was the precursor to secondary hydrocarbon and gold precipitation. Detailed petrography revealed the textures of particulate Au-U-C associations in the Witwatersrand Basin but elemental micro-mapping was necessary to determine the distribution of metals, major elements, trace elements and rare earth elements within carbon seams and carbon nodules. Carbonaceous materials were closely associated with disseminated elemental sulphur, mobile elements and rare earth elements. The occurrence of mobile elements and sulphur disseminated through the hydrocarbon suggested that the carbonaceous matter was formed from a fluid phase. Organic sulphur compounds in fluids derived from sedimentary organic matter are theorised to enhance the solubility of various metals in hydrocarbon phases. The occurrence of Au, As, Ag, Ti, V, U, Hg, Fe, Co, Cu, Cr, Mn and other metals in the hydrocarbons in the Basin indicated that a process other than radiolytic polymerisation may have been involved in the concentration of certain metals from a liquid phase. The similarity of metals concentrated in Witwatersrand carbonaceous matter to those of modern day crude oils and petroleum liquids derived from the degradation of Type I kerogens provided a potential mechanism for remobilisation in the Basin. These observed Au-U-C associations laid the foundation for experimental simulation. Catalytic Chemical Vapour Deposition experiments used acetylene and hydrogen gas to precipitate solid nanocarbon materials onto uranium-bearing powders. Results showed that for increasing uranium concentration, greater masses of carbonaceous materials were deposited onto the uranium-bearing powders. Therefore, carbonaceous product deposition was confirmed to be correlated with uranium concentrations. When uranium was leached out of the samples, the mass of carbon deposited was significantly decreased. The growth of carbon started at 300°C, was physically visible at 450°C and completely encapsulated the powders forming a product similar to Witwatersrand carbon seams at 600°C. Raman spectra indicated that the experimentally formed carbonaceous products had similar signatures to those of Witwatersrand carbon. The simulation of C-U associations was confirmed by electron microscopy, which showed that carbon nanotubes, carbon nanofibers and sheet-like materials precipitated onto uraninite grains under experimental conditions. These experimentally formed structures were comparable to those observed in Witwatersrand seam carbon, especially the sheet-like and fibrous/tube-like materials. It was suspected that gold distribution in carbon seams could provide useful data for hydrocarbon formation processes. Consequently micro-computed tomography, in conjunction with automated electron dispersive spectra, was used to examine the distribution of gold in three dimensions. The sample analysed was a carbon seam from the Carbon Leader Reef that contained exceptionally high gold grades. Gold in this carbon seam was found to occur most concentrated between carbon spindles in addition to small particles within spindles. Furthermore gold concentrations were highest at the footwall and hanging wall contacts and decreased towards the centre of the seam. The hydrocarbon spindle form also changed from bulbous at the contacts to more uniform and elongated in the centre of the carbon seam. It was therefore suggested that hydrocarbon growth and gold crystallisation in carbon seams was akin to crystal growth in quartz veins, where spindles are elongated parallel to the principal stress direction. In order to experimentally simulate Au-U-C associations, gold in solution at high pressures was required. Solvothermal experiments that used an autoclave and sucrose in solution were undertaken. Sucrose represented a common component found in petroleum liquids derived from Type I kerogens, similar to what is postulated for the Witwatersrand Basin. The experiments showed that hydrocarbons could precipitate at lower temperatures compared to temperatures observed in the Basin – c.a. 180°C. In addition, the effect of pressure was to enhance the breakdown of sucrose into more sheet-like carbonaceous products when 800 kPa of nitrogen gas was added to the reaction vessel. Finally, a solution of 0.01 M aurichloric acid was added to the experiments to determine if gold in solution would be precipitated during hydrocarbon precipitation. Results showed that almost all the gold was precipitated from solution as crystalline and nano-particulate gold. Strikingly, gold that precipitated was enclosed by hydrocarbons and was also seen to adhere onto the surfaces of sheet-like carbonaceous materials, indicating that the gold and hydrocarbon are intimately associated and that hydrocarbons facilitate the precipitation of gold from solution. Although experimental conditions could not match geological conditions exactly, the experimental products were comparable to the Witwatersrand Au-U-C associations. The results from this research show that catalytic electron promotion of uranium and other metals play an important role in hydrocarbon structuring and precipitation. The model of fluid remobilisation of hydrocarbons and gold is further enhanced by the evidence presented in this study. In conclusion, remobilisation textures were seen in the Au-U-C associations from the Witwatersrand Basin. Similar associations were experimentally precipitated using a hydrocarbon and gold-rich fluid
A thesis submitted to the Faculty of Science, University of the Witwatersrand, Johannesburg, in fulfilment of the requirements for the degree of Doctor of Philosophy, 2017
Keywords: Physical geology; Petrology--South Africa; Geology--South Africa